2022
DOI: 10.3390/agronomy12010150
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Distribution of Calcium (45Ca) Applied to the Surface of Orange (Citrus sinensis) Fruits at Different Developmental Stages

Abstract: In this study, the rate of absorption and transport of calcium (Ca) in orange fruits (Citrus sinensis cv. Fukumoto) after surface treatment with 45Ca was evaluated by supplying treatments at different dates between fruit set and mid-phase II of growth (i.e., 30, 44, 66 and 99 days after full bloom, DAFB). 45Ca absorption was always detected, but 45Ca application at the fruit set was associated with the highest rates of Ca transport into the pulp (39%) compared to the other treatments (17–19%). Scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The absorption peaks at 38 DAFB and may be antagonistic with nutrients such as potassium (K + ), ammonium (NH 4 + ), and magnesium (Mg 2+ ) at the early stage of fruit development. Similarly, Bonomelli et al (2022) find significant differences in calcium distribution in orange (Citrus sinensis) fruits cv. 'Fukumoto' with applications at various stages of development (30 DAFB, 44 DAFB, 66 DAFB, and 99 DAFB).…”
Section: Calcium Absorption By the Fruitsmentioning
confidence: 88%
See 2 more Smart Citations
“…The absorption peaks at 38 DAFB and may be antagonistic with nutrients such as potassium (K + ), ammonium (NH 4 + ), and magnesium (Mg 2+ ) at the early stage of fruit development. Similarly, Bonomelli et al (2022) find significant differences in calcium distribution in orange (Citrus sinensis) fruits cv. 'Fukumoto' with applications at various stages of development (30 DAFB, 44 DAFB, 66 DAFB, and 99 DAFB).…”
Section: Calcium Absorption By the Fruitsmentioning
confidence: 88%
“…Additionally, the influence of Ca on the contents of endogenous growth substances, especially cytokinins, has been reported (Ali et al, 2021). In this context, Bonomelli et al (2022) found that early applications of Ca were more effective in increasing the dry mass of orange fruits.…”
Section: Fruit Size and Massmentioning
confidence: 98%
See 1 more Smart Citation
“…In these organs, the higher Ca concentration in T1-Ca resulted in significant variations in Ca content compared to T2 trees, with no differences in biomass among treatments. According to Bonomelli et al [35], during fruit set, more Ca transport to the fruit pulp occurs (up to 39% of applied 45 Ca). However, as the fruit grows, more Ca is retained in the calyx zone, which decreases the rise in Ca in fruit (between 17 and 19% of applied 45 Ca).…”
Section: Effect Of Ca Fertilization On Ca Content Distribution In Cit...mentioning
confidence: 99%
“…We are able to ascertain this based on the use of labeled fertilizers with 44 Ca. In citrus fruit, the uptake and distribution of Ca deriving from fertilizers in "Clemenules" and "Fukumoto" mandarin trees have been studied using the isotope labeling technique with radioactive isotope 45 Ca [34,35]. This approach opens new possibilities for gathering insights into calcium nutrition in crops, offering a valuable alternative to radioactive isotopes.…”
Section: Introductionmentioning
confidence: 99%